Energy audit in a building / Mohamad Zaki Abadan - Abadan, Mohamad Zaki (2001)
Energy plays an important role in the development of a country. As such it needs a lot of efforts in the supply and the demand side to go hand-in-hand. Energy audit is a comprehensive method in checking the energy usage and wastage in buildings. This project presents the process of energy audit carried out at UiTM campus and the proposal made, to reduce the energy usage. Opportunities for improving the energy consumption were identified and evaluated. The economic analysis was carried out to determine the payback period. Good energy management should result in a reduction of usage by eliminating wastes and increasing efficiency.